Pengaruh Disiplin Kerja, Kompensasi, Motivasi Dan Pelatihan Terhadap Keputusan Kerja Karyawan Pada PT. BPRS Metro Madani Kantor Pusat - Ariyani, Khusnul Nisaa'; Febriyanto, Febriyanto (Universitas Muhammadiyah Metro, 2021)
This research aimed to know the effect among work discipline, compensation, motivation, and training simultaneously toward employee job satisfaction at PT. BPRS Metro Madani. This research used sample of 36 respondents from a population of 40 employees. Data analysis techniques using multiple linear regression, hypothesis testing and determination coefficient by using SPSS. Based on the research result that has been done, so it can be conclude that work discipline, compensation, motivation, and training simultaneously have a positive and significant effect toward employee job satisfaction at PT. BPRS Metro Madani. Keywords: Work Discipline, Compensation, Motivation, Training, Job Satisfaction